The Perception of Generation Z on Communication Ethics in Information Dissemination through Social Media - Eko Prasetyo Nugroho Saputro; Pratiwi Wahyu Widiarti; Wuri Handayani; Ratna Ekawati (Journal of Social Studies, 2025)
This study aims to describe Generation Z's perceptions of communication ethics in delivering messages on social media. Using a quantitative approach, the research was conducted with active students at Universitas Negeri Yogyakarta (UNY). The study employed multistage sampling, selecting 394 students from eight faculties: FIPP, FISHIPOL, FIKK, FT, FMIPA, FBSB, FEB, and FV. Data were collected through questionnaires distributed via Google Forms. The validity test indicated that six out of 32 items were invalid, leaving 26 valid items for further analysis. The reliability test yielded a coefficient of 0.858, signifying high reliability. Descriptive percentage statistical techniques were used for data analysis. Results showed that 51% of students had a high perception of communication ethics, while 49% had a low perception. Key aspects of communication ethics assessed included politeness in language, avoiding emotional triggers, caution in posting information, refraining from offensive content related to ethnicity, religion, race, and inter-group relations, and discretion in sharing personal photos. The study concludes that although most students display ethical awareness in their social media communication, nearly half still need improvement. It recommends enhancing educational programs and awareness initiatives to promote stronger ethical practices among Generation Z.